Report of the Oversight Committee on Reservation in Higher Educational Institutions Volume-I - Planning Commission (Planning Commission, 2006)
This report seeks to expand the provision of Higher Education while at the same time ensuring social inclusion and academic excellence. A society which excludes a significant section of its population from access to higher education cannot be said to be providing equality of opportunity. Equally, if academic excellence gets compromised in the process of expansion, it would lose its competitive edge in the emerging knowledge society - an edge which can propel India into a position of global leadership.
Government of India Planning Commission
Government of India Planning Commission